The Significance of the Multicultural Education Based on the Experiential Learning of a Local Community - Yun, Heejin; Juanjuan Zhang (European Journal of Social Science Education and Research, 2019)
The multicultural education was originally discussed in the Europe and the North America. It was introduced to South Korea more than 20 years ago and it has been discussed earnestly in South Korea. It began with the increase of Southeastern Asian immigrant workers and marriage-based immigrants in the late 1990s. People began to discuss the multicultural education as the awareness and demand regarding the human rights of immigrants, Korean language education, and the children of immigrants increased. Afterward, the multicultural education has become an education for the majority since the concept was extended to the society, although it once was conducted within the category of immigrants. The multicultural education, which has been taking place in South Korea, mostly consists of one-time experiential learning such as adding a multicultural element in a regular coursework, introducing other countries, or giving a chance to experience languages, foods, or clothes of other countries. The multicultural education utilizing the experiential learning is characterized by creative experiential activities, its association with the overall curriculum, and the connection with local communities. This study identified the significance of the multicultural education based on the experiential learning by examining the elements of the multicultural education.